2022
DOI: 10.1038/s41598-022-04910-y
|View full text |Cite
|
Sign up to set email alerts
|

Cycloidal CT with CNN-based sinogram completion and in-scan generation of training data

Abstract: In x-ray computed tomography (CT), the achievable image resolution is typically limited by several pre-fixed characteristics of the x-ray source and detector. Structuring the x-ray beam using a mask with alternating opaque and transmitting septa can overcome this limit. However, the use of a mask imposes an undersampling problem: to obtain complete datasets, significant lateral sample stepping is needed in addition to the sample rotation, resulting in high x-ray doses and long acquisition times. Cycloidal CT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For instance, [1] uses an initial bicubic interpolation to estimate missing data in the sinogram, which is then further improved using a U-net [2] deep neural network, whilst [3] uses a linear interpolation followed by a U-net. [4] also uses bicubic spline interpolation and convolutional neural network enhancement, whilst [5] uses bilinear interpolation followed by a regularisation performed during reconstruction, using the regularised primal-dual algorithm [6]. The common theme here is that standard interpolation methods are used followed by learned enhancement algorithms.…”
Section: Imagementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, [1] uses an initial bicubic interpolation to estimate missing data in the sinogram, which is then further improved using a U-net [2] deep neural network, whilst [3] uses a linear interpolation followed by a U-net. [4] also uses bicubic spline interpolation and convolutional neural network enhancement, whilst [5] uses bilinear interpolation followed by a regularisation performed during reconstruction, using the regularised primal-dual algorithm [6]. The common theme here is that standard interpolation methods are used followed by learned enhancement algorithms.…”
Section: Imagementioning
confidence: 99%
“…We train two networks to map 4 ) . This choice imposes two constraints on the NN design: it must have two input channels on the first layer and a network will always receive the input from the closest acquisition on the first channel of its input layer.…”
Section: B Design Of the Interpolation Networkmentioning
confidence: 99%
“…The achievable image quality depends on the number of acquisitions. With the help of advanced algorithms and using regularisation functions such as Total Variation (TV) to enforce certain image smoothness properties [1], or material heterogeneity [2], or learned, datadriven regularisations [3], [4], [5], [6], [7], a significant reduction in the number of measurements is possible, without a significant reduction in image quality. In fact, a range of recent papers has shown that even single projection images are sufficient in certain settings to identify one known image out of a small set of possible reconstructions [8], though this only works by imposing very strong prior constraints, which is only possible if the objects are extremely predictable in their 3D shape.…”
Section: Introductionmentioning
confidence: 99%